Correction of anterior crossbite using modified transparent aligners: An esthetic approach - K Korath Abraham; Arun Roy James; Elza Thenumkal; Tharian Emmatty (Wolters Kluwer Medknow Publications, 2016)
Anterior crossbite results from the abnormal axial inclination of one or more anterior teeth. It is a major esthetic and functional anomaly which has to be corrected in the primary and early mixed dentition period to allow the normal development of maxilla and mandible as well as the occlusion. Several treatment options are available to correct the problem. A unique appliance, "modified transparent tray aligners" was used to correct the anterior crossbite in an 8-year-old child. The clinical presentation, fabrication of the appliance, and the outcome are discussed.